Crosstalk Between Long Non-coding RNAs, Micro-RNAs and mRNAs: Deciphering Molecular Mechanisms of Master Regulators in Cancer - López-Urrutia, Eduardo; Bustamante Montes, Lilia P.; Ladrón de Guevara Cervantes, Diego; Pérez-Plasencia, Carlos; Campos-Parra, Alma D. (Frontiers in Oncology, 2019)
Cancer is a complex disease, and its study requires deep understanding of several biological processes and their regulation. It is an accepted fact that non-coding RNAs are vital components of the regulation and cross-talk among cancer-related signaling pathways that favor tumor aggressiveness and metastasis, such as neovascularization, angiogenesis and vasculogenic mimicry. Both long non-coding RNAs (lncRNAs) and micro-RNAs (mi-RNAs) have been described as master regulators of cancer on their own; yet there is accumulating evidence that, besides regulating mRNA expression through independent mechanisms, these classes of non-coding RNAs interact with each other directly, fine-tuning the effects of their regulation. While still relatively scant, research on the lncRNA-miRNA-mRNA axis regulation is growing at a fast rate, it is only in the last five years, that lncRNA-miRNA interactions have been identified in tumor-related vascular processes. In this review, we summarize the current progress of research on the cross-talk between lncRNAs and miRNAs in the regulation of neovascularization, angiogenesis and vasculogenic mimicry.